Growth of a Western Tarai District Headquarter: A Case Study of Parasi Bazar From 1978 to 1996 - Rajbanshi, Ashok (Tribhuvan University Journal, 2010)
Not available.Key words: Growth of Western Tarai; Parasi Bazar; History; Nepal Tribhuvan University Journal Vol. XIX, No. 2, 1996 Page: 43-56 Uploaded Date: 29 October, 2010